Self-acceptance and acceptance of others an Afrikaans version of the Berger scales - Bergemann, Niels (South African journal of psychology, 1988)
In the context of the increasing relevance of self-concept research, this study was concerned with the development of an Afrikaans version of Berger's (1952) Questionnaire for Assessing Self-Acceptance and Acceptance of Others, and with aspects of the validation of these scales. The scales, developed in the USA, were translated into Afrikaans and were tested on a sample of 219 college students. The questionnaire was reduced by means of item and factor analysis which resulted in a reduced Afrikaans version with 31 items, 21 for assessing Self-Acceptance, and 10 for the Acceptance of Others scale. The internal homogeneity of both scales was examined by an NMDS. The external validity of both scales was verified by considering them in relation to the scales of the EPI. Possible further applications of the Berger scales were discussed.